The Elementary School Learning Management at SD Negeri Sewukan Magelang - Budiharto, Budiharto (2011)
There are three objectives of this research. The first objective is identifying the characteristics of elementary school learning preparations at SD Negeri Sewukan Magelang. Second, this research describes the characteristics of teachers' activities in elementary school learning at SD Negeri Sewukan Magelang. Third, it classifies the characteristics of students' activities in elementary school at SD Negeri Sewukan Magelang. It is a descriptive qualitative research with ethnography design. The research is done in SD Negeri Sewukan Magelang. It is located in Disaster Risk Area III. The society in this area must be evacuated from the place where disaster of natural phenomenon is happened. Techniques used in data collection are in-depth interview, observation, and documentation. Data analysis of this research is collecting data, composition, classify, describe, and discussion. Based on the analyzed data, the writer has three main findings. They are (1) the elementary school learning preparation at SD Negeri Sewukan Magelang is planned and programmed based on the discussion of all related parties, (2) the teachers' activities at elementary school learning are begun by making learning scenario, checking the member of the students and tools, debriefing and the implementation that are adapted with each phases, and (3) the students' activities at elementary learning are done by playing, drawing, writing, and making handicraft.